2014
DOI: 10.1267/ahc.14003
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Dihydroxybenzaldehyde Derived from <i>Prunus mume</i> Seed Inhibits Oxidative Stress and Enhances Estradiol Secretion in Human Ovarian Granulosa Tumor Cells

Abstract: Granulosa cells form ovarian follicles and play important roles in the growth and maturation of oocytes. The protection of granulosa cells from cellular injury caused by oxidative stress is an effective therapy for female infertility. We here investigated an effective bioactive compound derived from Prunus mume seed extract that protects granulosa cells from hydrogen peroxide (H2O2)-induced apoptosis. We detected the bioactive compound, 3,4-dihydroxybenzaldehyde (3,4-DHBA), via bioactivity-guided isolation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…PA has been demonstrated to have anti-inflammatory activities 32 , neuroprotective effects against oxidative stress 33 and anti-cancer activities 34 . We also reported that PA has the potential to attenuate oxidative stress in human granulosa cells 23 . PA also inhibited both antigen-induced intracellular Ca 2+ mobilization and membrane ruffling but not non-IgE-mediated degranulation, similar to VA.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…PA has been demonstrated to have anti-inflammatory activities 32 , neuroprotective effects against oxidative stress 33 and anti-cancer activities 34 . We also reported that PA has the potential to attenuate oxidative stress in human granulosa cells 23 . PA also inhibited both antigen-induced intracellular Ca 2+ mobilization and membrane ruffling but not non-IgE-mediated degranulation, similar to VA.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, it has been reported that the effect of oestradiol on anaphylaxis in mouse is related to enhanced vascular permeability, which is associated with oestradiol-mediated upregulation of endothelial nitric oxide synthase (eNOS) and nitric oxide (NO) 38 . The effect of ume and ume -related products suggested by the results of our study using human ovarian granulosa cell lines have been considered to be a regulation of sex hormone secretion 23 . From these views, ume intake may not only inhibit mast cell degranulation but also may influence the regulation of oestradiol or affect the regulation of oestradiol-mediated eNOS and NO, thereby exerting an anti-allergic effect in women.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…DHB also has anti‐inflammatory properties, neuroprotective effects and protects against cerebral ischemia . DHB protects the granulosa cells from hydrogen peroxide induced apoptosis and has shown clinical potential for the cure and prevention of female infertility …”
Section: Introductionmentioning
confidence: 99%